Differences in Ureolytic Bacterial Composition between the Rumen Digesta and Rumen Wall Based on ureC Gene Classification - Jin, Di; Zhao, Shengguo; Zheng, Nan; Bu, Dengpan; Beckers, Yves; Denman, Stuart E.; McSweeney, Christopher S.; Wang, Jiaqi (Frontiers in Microbiology, 2017)
Ureolytic bacteria are key organisms in the rumen producing urease enzymes to catalyse the breakdown of urea to ammonia for the synthesis of microbial protein. However, little is known about the diversity and distribution of rumen ureolytic microorganisms. The urease gene (ureC) has been the target gene of choice for analysis of the urea-degrading microorganisms in various environments. In this study, we investigated the predominant ureC genes of the ureolytic bacteria in the rumen of dairy cows using high-throughput sequencing. Six dairy cows with rumen fistulas were assigned to a two-period cross-over trial. A control group (n = 3) were fed a total mixed ration without urea and the treatment group (n = 3) were fed rations plus 180 g urea per cow per day at three separate times. Rumen bacterial samples from liquid and solid digesta and rumen wall fractions were collected for ureC gene amplification and sequencing using Miseq. The wall-adherent bacteria (WAB) had a distinct ureolytic bacterial profile compared to the solid-adherent bacteria (SAB) and liquid-associated bacteria (LAB) but more than 55% of the ureC sequences did not affiliate with any known taxonomically assigned urease genes. Diversity analysis of the ureC genes showed that the Shannon and Chao1 indices for the rumen WAB was lower than those observed for the SAB and LAB (P < 0.01). The most abundant ureC genes were affiliated with Methylococcaceae, Clostridiaceae, Paenibacillaceae, Helicobacteraceae and Methylophilaceae families. Compared with the rumen LAB and SAB, relative abundance of the OTUs affiliated with Methylophilus and Marinobacter genera were significantly higher (P < 0.05) in the WAB. Supplementation with urea did not alter the composition of the detected ureolytic bacteria. This study has identified significant populations of ureolytic WAB representing genera that have not been recognized or studied previously in the rumen. The taxonomic classification of rumen ureC genes in the dairy cow indicates that the majority of ureolytic bacteria are yet to be identified. This survey has expanded our knowledge of ureC gene information relating to the rumen ureolytic microbial community, and provides a basis for obtaining regulatory targets of ureolytic bacteria to moderate urea